The linguistic rooting of a (reactive) structure in the Holy Qur’an is a phonemic-morphological approach (Journal of the College of Basic Education, 2022)
The name of the machine is one of the old new topics, which research has not been closed, and researchers and scholars still seek new weights for it, and put up-to-date names for it that have no control and no origin, due to the relationship of this name with the changes of the era and its modernity and rapid development due to the development of industry And the multiplicity of instruments that reflect a state of community well-being and civilization, but we find that the Noble Qur’an is full of the names of the well-known and used instruments so far: such as the scale, the key and the lamp, and others or a few neglected at the present time such as the manna, the Al-Sawaa, etc. And what was rigid and has no basis or control, such as a coffin and a stick.This study deals with a weight of the machine's name weights differently from what it preceded, as it deals with it from its linguistic root, its sounds and its relationship to the meaning, then it moves to the morphological structures to shed light on it in particular on machine building, and what it relates to in the Qur’anic usage, and this study has reached several data And important indications that must be highlighted in detail in the folds of the research, and summarize them with a clear conclusion at the conclusion of the research, noting that the study did not accommodate the weights (active) contained in the Qur’an, so the aim of the study was not statistical, but rather authentic in most of its aspects.The research looked in the context of the complete surah when it followed the sayings of the commentators, and therefore we find that it sometimes prefers the context of the surah to the consensus of the commentators, as in the formula (mihrab) in Surat Saba, which is the name of a machine for what is being fought with, any type of weapon, and not, as most went, as rooms or retreats. Because the context of the surah and the specifics of the verses mentioned - as we have detailed in the research - confirm that what is meant by (the mihrab) is a type of weapon.One of the accuracy of the Qur’anic usage explained by the research is that it comes in two terms that seem to be synonymous, but the Qur’an mentioned each of them for an intended purpose, as in (Weights and Measures). They are intended by themselves.Finally, the research was interested in the true origin of the words that came on zenah (verbal), And he was able to state that some of them were not of Arab origin. Rather, the origins varied between Abyssinian, Surrealist and Hebrew, The Qur’anic use of these terms was sometimes correlated with the peculiarities of Maqam, which the research referred to in detail